Role of fibroblast growth factors in pulmonary parenchymal and vascular remodeling - Schwind, Felix Johannes Maria; Justus Liebig University Giessen (My University, 2022)
Fibroblast growth factors (FGFs) are a family of evolutionary related polypeptides, involved in a multitude of developmental and regenerative pathways in vertebrates. While they serve as essential growth and differentiation factors during embryogenesis and are crucial for maintaining homeostasis in the adult organism, aberrant FGF-signaling is also deeply enrooted within a wide number of pathologies. Idiopathic pulmonary arterial hypertension (IPAH) and idiopathic pulmonary fibrosis (IPF) are hyperproliferative, nonmalignant pulmonary diseases, which both feature dysregulated and excessive cell proliferation in their pathogenesis. Although separate entities, they seem linked through their pathomechanisms, in which inflammatory and proliferative stimuli, in part mediated through various cytokines and growth factors, promote detrimental alterations of the pulmonary parenchyma and vasculature. If left untreated, these alterations ultimately lead to impaired gas exchange, loss of cross-sectional area and increased pressure within the pulmonary circulation. Despite readily available treatment regimens and growing insight into the pathophysiology, both conditions are still associated with a significantly reduced life expectancy. The involvement of fibroblast growth factors in IPF and IPAH is ambiguous and somewhat conflicting. In animal models, heightened levels of the prototypical FGFs,FGF1 and FGF2, were associated mostly with baneful effects in the form of proliferating pulmonary smooth-muscle cells, vasoconstriction and the profibrotic accumulation of myofibroblasts. In contrast, increased expression of FGF7 and FGF10 protected against the development of pulmonary hypertension in rats and mitigated bleomycin-induced lung fibrosis in mice. Furthermore, FGF7 has been shown to promote the proliferation of AEC2 and even prevented pulmonary injury in animals, suggesting an overall protective effect on the alveolar epithelium. The author therefore hypothesized, that the expression of FGF7, FGF10 and FGFR2 would be altered in the course of IPF/ IPAH and aimed to further investigate, whether these alterations contribute to disease progression or rather represent an intrinsic attempt at regeneration and restoring homeostasis. Applying the techniques of immunohistochemistry, human lung tissue samples from patients with IPF and IPAH were analyzed for the expression patterns of FGF7, FGF10, FGFR1 and FGFR2, which then were compared to patterns found in healthy donor tissue. Our results demonstrate a marked increase in the overall expression of FGF7, FGF10 and FGFR2 in both, IPAH and IPF lungs, compared to donors. An in-depth analysis of the signal distribution revealed signal maxima confined to the remodeled parenchyma and vasculature. In IPF lungs, areas of mature fibrosis consistently featured strong immunoreactivity, while sites of early fibrosis (“fibroblastic foci”) displayed only light, occasional signal. Considering all the data presented in this study, we deduct that FGF7/FGF10-FGFR2 signaling is altered in the context of pulmonary remodeling, but is likely not the instigator. Follow-up observations indicated that FGF10 expression correlates with disease severity in IPF, which is compatible with our perception of the FGF10-FGFR2 signaling pathway as an “ineffective antifibrotic mediator”. Additional research regarding the significance of this pathway and potential benefits of its extrinsic stimulation in the context of pulmonary remodeling is duly needed. Especially, as current treatment options for IPF are primarily based on the inhibition of receptor tyrosine kinases and likely also inhibit FGFR2 signaling, mitigating any potentially antifibrotic effects of the FGF7/FGF10-FGFR2 signaling pathway. During the second half of this study, focus has been turned to the alveolar lipofibroblast. There has been general consensus about the existence of these cells in rodents, where they maintain a close relationship with AEC2, storing and trafficking neutral-lipids for surfactant synthesis and protecting the lung against oxidant injury. At distinct phases during embryonic lung development in mice, FGF10-positive progenitor cells give rise to myofibroblasts and lipofibroblasts, the latter having demonstrated the tendency to later undergo a phenotypic shift into myofibroblasts in response to injurious stimuli. Myofibroblasts are generally regarded as the main effector cells of pulmonary remodeling in IPF and our group has identified lipofibroblast to-myofibroblast transdifferentiation as one source of activated myofibroblasts in the bleomycin mouse-model of fibrosis. In order to determine whether a similar phenotypic shift could be involved in the pathogenesis of IPF, we aimed to confirm the presence of alveolar lipofibroblasts in the human lung, where their existence has been controversial. Through utilization of the fluorescent neutral lipid stain “LipidTOX” on human lung tissue, we were able to gather strong evidence for neutral-lipid containing cells in close proximity to AEC2 – in both, donor and IPF lungs. Subsequent investigations by our group confirmed that these cells are resident and likely lipofibroblasts. Considering the data presented by this study and reports of decreased lipofibroblast- and increased myofibroblast-markers in IPF lungs, the transdifferentiation of lipofibroblasts to myofibroblasts appears to be an underlying principle in the human condition as well. Our group proposed that this transdifferentiation is likely facilitated by TGF-β1, while PPARγ seems to stabilize and reinforce the lipogenic phenotype, which can be considered a significant advance towards a deeper understanding of the molecular principles of IPF. PPARγ agonists and even metformin might therefore embody a way to counteract this detrimental shift during fibrosis formation or even later on. In conclusion, alveolar lipofibroblasts have not only been identified as progenitors of the primary effector cells of remodeling in IPF, they also represent a novel pharmacological target, which might ultimately lead to new options in the treatment of patients with IPF.
Keywords: ddc:610